Investigation of Live Attenuated Measles Virus Vaccine as Anti Tumor Agent - Ismaee, Farah E; Al-Shammari, Ahmed M; Salih, Shahlaa M (Al-Nahrain Journal of Science, 2018)
This study was carried out to evaluate the antitumor effect of live attenuated measles virus Schwarz (MV) vaccine strain on tumor cell lines in vitro. Live attenuated measles virus Schwarz vaccine strain was obtained from Aventis Pasteur, France. Live attenuated measles virus Schwarz strain was propagated on Vero, human Rhabdomyosarcoma (RD) and human Glioblastoma-Multiform (GBM) cell lines which were supplied by Iraqi Center for Cancer and Medical Genetic Researches (ICCMGR). Results revealed that cell fusion occurred after 24 h of infection. The infected confluent monolayer appeared to be covered with syncytia with granulation and vaculation of cells after 72 to 120 h. Moreover, the formation of large round empty plaque spaces was observed in infected cells. Results of oncolytic cytopathic effect showed that after 120 h of exposure alterations in morphology of Vero, RD and GBM cells. Cells were rounded, shrink, clustered cells and large empty space with cell debris as a result of cell lysis and death. Haemadsorption effect of MV was studied and result recorded that all cell lines infected with virus have the ability for haemadsorption human red blood cells after 72 h of infection. While uninfected cells gave negative results. Detection of MV H protein by monoclonal antibodies in infected cells of all cell lines by immunocytochemistry assay gave positive results (brown color) in cytoplasm of infected cells. Cell viability was measured after 72 h of infection by MTT assay. Results showed a significant cytotoxic effect for measles virus (P ≤0.05) on growth of RD and GBM cell lines at the first dilution and the second one after 72 h of infection. When the dilution increases, there was a significant decline in the inhibitory effect with a significant cytotoxic effect as compared with the control. Also, concentrated inoculums of measles virus showed a significant cytotoxic effect when compared with the control.